Determinants of Corporate Social Responsibility Disclosure: Empirical Evidence from Indonesia Stock Exchange - Dita Ayu Lestari; Noegrahini Lastiningsih; Shinta Widyastuti (Information Management and Business Review, 2021)
This study aims to examine the relationship between consumer proximity, environmental performance, profitability, and media exposure on corporate social responsibility disclosure. This study used data from companies listed in Indonesia Stock Exchange (IDX) 2017-2019. A purposive sampling method was used in this study with 60 samples on the Indonesia Stock Exchange. Hypothesis testing in this study using multiple linear regression with SPSS. The results show that consumer proximity has a positive effect on corporate social responsibility disclosure. Meanwhile, environmental performance, profitability, media exposure does not affect corporate social responsibility disclosure. The implication of this study is for the companies to increase social responsibility to the stakeholders and community due to the positive reciprocal relationship.